Design and field procedures for the clinical reappraisal of the Composite International Diagnostic Interview version 3.3 in Qatar's national mental health study - Iman Amro (13996378) (2023)
Background The Composite International Diagnostic Interview (CIDI) has been clinically reappraised in several studies conducted mainly in the US and Europe. This report describes the methodology used to conduct one of the Middle East's largest clinical reappraisal studies. The study was carried out in conjunction with the World Mental Health Qatar—the first national psychiatric epidemiological study of common mental disorders in the country. This study aimed to evaluate the diagnostic consistency of core modules of the newly translated and adapted Arabic version of the CIDI 5.0 against the independent clinical diagnoses based on the Structured Clinical Interview for DSM‐5 (SCID‐5). Methods Telephone follow‐up interviews were administered by trained clinicians using the latest research edition of the SCID for DSM‐5. Telephone administered interviews were key in the data collection, as the study took place during the COVID‐19 pandemic. Results Overall, within 12 months, 485 interviews were completed. The response rate was 52%. Quality control monitoring documented excellent adherence of clinical interviews to the rating protocol. Conclusions The overall methods used in this study proved to be efficient and effective. For future research, instrument cultural adaptation within the cultural context is highly recommended. Other Information Published in: International Journal of Methods in Psychiatric Research License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/mpr.1958